Vernacular Typography Design of Bamboo Keben Craft as an Opportunity of Creating Digital Typeface - Sari, Ni Luh Desi In Diana; Mudra, I Wayan; Sarjani, Ni Ketut Pande (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Keben for the Balinese is a medium that functions to package ceremonial facilities made of bamboo. Craftsmen in Kayubihi village, Bangli sub-district produce kebens with various designs of vernacular typography motifs that have the opportunity to be developed in the form of digital typefaces. This study aims to: (1) analyze the vernacular typographic design of the keben motif and its opportunities in the creation of digital typefaces; (2) analyze the meaning of keben in Kayubihi village in a socio-cultural context. Qualitative methods are used in this study. Typographic design principles consisting of legibility, readability, visibility, and clarity are used to analyze the vernacular typography of the keben motifs, while Saussure’s semiotic approach is used to give meaning to the keben of Kayubihi village from the spirit and the concept behind it. Data collection strategies were carried out by observation and interviews, online and offline. Meanwhile, data analysis was carried out by interpreting, namely interpreting in-depth the collected data according to the research objectives. The results show that the vernacular typography of the keben motifs was arranged alphabetically to form words as a symbol of identity. Geometric motifs inspired by the environment around the craftsmen can be classified into five groups: the sun, flowers, traditional fabrics, objects, and cultural symbols of Balinese Hinduism. These motifs can be developed into digital typefaces. Keben in Kayubihi village spiritually means creativity, preservation of culture and identity. This creativity can be used as a source of inspiration in designing typefaces that offer novelty. The vernacular typography design with the Keben motif is indigenous creativity, representing the identity of the local Balinese culture.